An Economic Analysis of Investor Protection in Corporations With Concentrated Ownership - Morten Bennedsen; Daniel Wolfenzon (Copenhagen Business School (CBS), Department of Economics, 2000)
– We provide a theoretical analysis of the relationship between investor protection and the performance of corporations with concentrated ownership and apply it to analyze two types of investor protection. First, we analyze the cost and benefits of imposing super-majority requirements on certain important policy issues in the corporation. Second, we analyze why it can be in the interest of the corporation to impose restrictions on the free transferability of shares.
hdl:10398/7551
Keywords: G31; 330; Investor protection; Concentrated ownership; Corporate performance